Markers of Oxidative Damage and Antioxidant Enzyme Activities as Predictors of Morbidity and Mortality in Patients With Chronic Heart Failure - Radovanovic, Slavica; Savic-Radojevic, Ana; Pljesa-Ercegovac, Marija; Djukic, Tatjana; Suvakov, Sonja; Krotin, Mirjana; Simic, Dragan V.; Matic, Marija; Radojicic, Zoran; Pekmezovic, Tatjana; Simic, Tatjana (Journal of cardiac failure, 2012)
Although the majority of previous findings unequivocally confirmed the existence of systemic oxidative stress in chronic heart failure (CHF) patients, data on prognostic potential of biomarkers of oxidative lipid and protein damage are limited. We aimed to address the relation of oxidative stress markers to severity and prognosis in CHF secondary to ischemic cardiomyopathy. Plasma malondialdehyde (MDA), protein thiol groups (P-SH), reactive carbonyl derivatives (RCD), together with glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) activities were determined in 120 CHF patients and 69 healthy controls. Increased lipid peroxidation (MDA) and oxidation of plasma proteins (RCD; P-SH) s well as downregulated GSH-Px activity were found in CHF patients compared with controls. Significant correlation was obtained only for RCD content and remodeling indices (LVEDV: r = 0.469, P = .008; LVESV: r = 0.452; P = .011). Cox regression analysis demonstrated only MDA (HR = 3.33; CI: 1.55–7.12; P = .002) as independent predictor of death, whereas SOD was associated with unstable angina pectoris (HR = 2.09; CI: 1.16–3.78; P = .011). In the course of CHF progression, carbonyl stress is implicated in the LV remodeling. Malondialdehyde level might be a useful parameter for monitoring and planning management of CHF patients.